Clinical Features of Myasthenia Gravis With Antibodies to MuSK Based on Age at Onset: A Multicenter Retrospective Study in China - Zhou, Yufan; Chen, Jialin; Li, Zunbo; Tan, Song; Yan, Chong; Luo, Sushan; Zhou, Lei; Song, Jie; Huan, Xiao; Wang, Ying; Zhao, Chongbo; Zeng, Wenshuang; et al. (Frontiers in Neurology, 2022)
Introduction: Antibodies to MuSK identify a rare subtype of myasthenia gravis (MuSK-MG). In western countries, the onset age of MuSK-MG peaks in the late 30’s while it is unknown in Chinese population. Methods: In this retrospective multicenter study, we screened 69 MuSK-MG patients from 2042 MG patients in 5 tertiary referral centers in China from October 2016 to October 2021 and summarized the clinical features and treatment outcomes. Then we subgrouped the patients into early-onset (<50years old), late-onset (50-64 years old), and very-late-onset (≥65 years old) MG and compared the differences in weakness distribution, disease progression and treatment outcomes among three subgroups. Results: The patients with MuSK-MG were female-dominant (55/69) and their mean age at onset was 44.70±15.84 years old, with a broad range of 17-81 years and bimodal distribution at 20-40 years and 40-70 years old. At disease onset, 29/69 patients were classified as MGFA Type IIb and the frequency of bulbar and extraocular involvement was 53.6% and 69.6%, respectively. There was no difference in weakness distribution. Compared with early-onset MuSK-MG, very-late-onset patients had a higher proportion of limb muscle involvement (12/15 vs.16/40, p = 0.022) 3 months after onset. Six months after onset, more patients with bulbar (14/15 vs.26/39, p = 0.044) and respiratory involvement (6/15 vs.0/13, p = 0.013) were seen in very-late-onset than in late-onset subgroup. The very-late-onset subgroup had the highest frequency of limb weakness (86.7%, p < 0.001). One year after onset, very-late-onset patients demonstrated a higher frequency of respiratory involvement than early-onset patients (4/12 vs. 2/35, p = 0.036). 39/64 patients reached MSE. Among 46 patients who received rituximab, very-late-onset patients started earlier than late-onset patients (6 (5.5-7.5) vs.18 (12-65) months, p = 0.041), but no difference in the time and rate to achieving MSE was identified. Conclusion: MuSK-MG patients usually manifested as acute onset and predominant bulbar and respiratory involvement with female dominance. Very-late-onset patients displayed an early involvement of limb, bulbar and respiratory muscles in the disease course, which might prompt their earlier use of rituximab. The majority MuSK-MG patients can benefit from rituximab treatment regardless of age at onset.